Using visual analysis in tourism attraction management of puncak menara api gunung Saribu village, Munte district, Karo regency - Sofyan, Rudy; Ginting, Junita Setiana; Sinulingga, Samerdanta (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Puncak Menara Api in Gunung Saribu Village, Munte Sub-District, Karo Regency, is a buffer zone of the protected forest area in Karo Regency. In 2020, all the local communities through village funds are trying to pioneer the development of Puncak Menara Api as a new tourist attraction. In relation to such an effort, the community service team of Universitas Sumatera Utara assisted the people in Gunung Saribu Village in creating the concept of developing Puncak Menara Api as a nature-based and education-based tourist attraction in Karo Regency. The assistance includes but not limited to improving the capacity of tourism management for rural communities, mapping the tourist sites, marketing the tourist sites, and so forth. For the many development activities items that must be done, the team selected mapping tourist sites as the only activity to be carried out in 2020. This study was conducted using a qualitative method. The data were collected using focus group discussion, observation, and interview techniques. The data were analyzed using visual analysis, including visualizing the point object attributes, visualizing point object distribution, and visualizing spatial groupings. The results of the study are: (i) the visualization on the point object attributes finds four main components related to tourism: Attractions, Accessibility, Amenities, and Ancillary Services; (ii) the visualization on the point object distribution results in predicting the initial picture of the arrangement of tourist attractions in Puncak Menara Api; and (iii) the visualization on the spatial groupings results in designing the tourist location in a three-dimensional design.